2019
DOI: 10.1093/inthealth/ihz033
|View full text |Cite|
|
Sign up to set email alerts
|

The Traveller’s Risk Perception (TRiP) questionnaire: pre-travel assessment and post-travel changes

Abstract: Background Travellers’ risk perception is a key component of travel risk assessment because it influences the adequate implementation of safety precautions. The aims of this study are to validate a tool to analyse travellers’ risk perception to identify which factors can influence it and how it changes upon return. Methods The Traveller’s Risk Perception (TRiP) questionnaire was developed and administered to outpatients befor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…The results prove that there is indeed a significant difference between tourists’ risk perceptions of the destination before and after travel. The findings are consistent with those of Tardivo et al ( 2020 ), Xie et al ( 2020 ), and Zimmermann et al ( 2013 ). In addition, the social amplification of risk framework states that risk events can intensify or attenuate public risk perceptions in interaction with psychological, social and cultural processes (Kasperson et al, 1988 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results prove that there is indeed a significant difference between tourists’ risk perceptions of the destination before and after travel. The findings are consistent with those of Tardivo et al ( 2020 ), Xie et al ( 2020 ), and Zimmermann et al ( 2013 ). In addition, the social amplification of risk framework states that risk events can intensify or attenuate public risk perceptions in interaction with psychological, social and cultural processes (Kasperson et al, 1988 ).…”
Section: Discussionsupporting
confidence: 92%
“…For example, Zimmermann et al ( 2013 ) used a visual psychometric test to survey 314 travellers to tropical and subtropical destinations on nine health risk perceptions before and after travel. Tardivo et al ( 2020 ) used a questionnaire and telephone interviews to examine the changes in tourist perceptions of 8 health risks before and after travel during medical tourism. Xie et al ( 2020 ) distinguished between pretravel and post-travel risk perceptions when exploring the moderating effect of public opinion on risk perceptions and found that as tourists gained actual first-hand experience of the destination, their perceptions of the five types of risks were effectively corrected after travel.…”
Section: A Review Of Research On Identification Of Tourists’ Risk Per...mentioning
confidence: 99%
“…Travellers’ risk perception usually sees the traveller as the victim of adversity [ 115 ]. Scales have been used to predict risk behaviour [ 116 ].…”
Section: Safety and Securitymentioning
confidence: 99%